2007
DOI: 10.1128/jvi.02432-06
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Minor Groove Recognition of TA Base Pairs Is Required for Template Melting by the E1 Initiator Protein

Abstract: Template melting is an essential step in the initiation of DNA replication, but the mechanism of template melting is unknown for any replicon. Here we demonstrate that melting of the bovine papillomavirus type 1 ori is a sequence-dependent process which relies on specific recognition of TA base pairs in the minor groove by the E1 initiator. We show that correct template melting is a prerequisite for the formation of a stable double hexamer with helicase activity and that ori mutants that fail to melt correctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…We have shown that E1 binds to a dsDNA ori probe, forming a double trimer (DT); this DT is converted into a DH, which unwinds the template in the presence of E. coli single-strand DNA-binding protein (SSB), resulting in ssDNA+SSB complexes that can be detected by EMSA. This reaction is dependent on the formation of the E1 DH, which in turn is dependent on the centrally located E1 binding sites (BSs) and sequences on the flanks of the E1 BS (3,21,22). If both strands of the DNA pass through the central channel of the helicase, we expect that a streptavidin attached to either the 5′ or 3′ end of the DNA would be displaced, whereas if only one strand passes through the central channel, only streptavidin attached to that strand would be displaced.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that E1 binds to a dsDNA ori probe, forming a double trimer (DT); this DT is converted into a DH, which unwinds the template in the presence of E. coli single-strand DNA-binding protein (SSB), resulting in ssDNA+SSB complexes that can be detected by EMSA. This reaction is dependent on the formation of the E1 DH, which in turn is dependent on the centrally located E1 binding sites (BSs) and sequences on the flanks of the E1 BS (3,21,22). If both strands of the DNA pass through the central channel of the helicase, we expect that a streptavidin attached to either the 5′ or 3′ end of the DNA would be displaced, whereas if only one strand passes through the central channel, only streptavidin attached to that strand would be displaced.…”
Section: Resultsmentioning
confidence: 99%
“…For DnaA and systems like the eukaryotic Origin Recognition Complex (ORC), both of which belong to the same AAAϩ subgroup, the conformation, assembly, and origin recognition properties of the initiator all can be altered by ATP (17, 31, 48 -51). For the more distantly related SFIII helicases, a group of AAAϩ proteins that serve as initiators for certain dsDNA viruses, ATP is required for DNA melting as it is for DnaA (52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of this species to the active double-hexamer correlates with 'melting' activity and depends upon an aromatic residue on the DNA-binding hairpin of the helicase [42 ]. The melting activity is ATP-dependent [91 ], and could potentially utilize the same molecular motions described for the formed hexamer operating in a limited, local manner. Additional structural snapshots and biochemical investigation will address these questions.…”
Section: Concluding Remarks -Future Challengesmentioning
confidence: 99%